The Impact of Corporate and Shari’ah Governance on the Risk Profile of Islamic Financial Institutions - Muhammad Akmal; Syed Muhammad Abdul Rehman Shah; Awais ur Rehman; Muhammad Shehryar (Bank Indonesia, 2026)
This study analyzes the effects of corporate and Shari’ah governance on risk-taking practices in Islamic financial institutions in Pakistan. It also investigates the role of institutional quality in moderating these effects. A sample of 28 institutions over the period 2011–2022, including Islamic commercial banks, Takaful operators and Modarba companies, was utilized for the analysis. Applying the generalized method of moments (GMM) estimator, the results suggest that several individual characteristics of corporate governance and its index are significantly related to Shari’ah non-compliance and solvency risk. The findings also reveal that institutional quality significantly contributes to the lowering of risk. It is recommended that modern corporate and Shari’ah governance practices be adopted to manage both Shari’ah non-compliance and solvency risk.